The Moderating Effect of Digital Nudging and Gender on Online Student Commitment During the Digital Transformation Era, A Case Study at Arab Academy for Science, Technology and Maritime Transport - Nouran Ahmed Nashaat; Marwa Tarek Abd El Azeem Ahmed; Rasha Abd El Aziz Shalaby (Communications of International Proceedings, 2021)
The present study uses a proposed model to explore the impact of academic self-efficacy on satisfaction and commitment of students in higher education moderated by digital nudging and gender in an online learning environment. First, it presents academic self-efficacy and its impact on both student satisfaction and commitment. Second, it examines the significance impact of each of the moderating variables namely digital nudging and gender on both student satisfaction and commitment online. A sample of 410 students enrolled in an Egyptian higher education institution pursued an online questionnaire through Survey Monkey. This study used structured equation model approach for data analysis that was gathered online as well as telephone interviews. However, there was no significant impact of digital nudging on both student satisfaction and commitment while gender had a moderating effect on both student satisfaction and commitment. Specifically, academic self-efficacy had a significant influence on student satisfaction as well as student commitment. In addition, the mediating role of student satisfaction was tested and had positive influence between academic self-efficacy and student commitment. The study highlights the issue of commitment as a behavior of students and their satisfaction moderated with some variables. The context was limited to one higher education institution during the pandemic of COVID-19. Further research is needed to investigate the same model in other higher educational institutions in Egypt and could be extended to other countries if possible.
Keywords: Commitment; Gender; Academic Self-Efficacy; Higher Education.